Downsizing in German chemical manufacturing industry during the 1990s: why small is beautiful? - Oleg Badunenko (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
German chemical manufacturing industry is marked by two major structural changes during 1992-2004. Firstly, number of firms was ranging extensively: from 676 to 901, while only 96 firms represented balanced panel. Secondly, size of the firm dropped considerably-by 88%. This paper is intended to shed light on both phenomena. Based on reliable census data analysis suggests the former evidence be explained (i) by persistent poor performance of firms and (ii) by so called general purpose technology argument. The latter phenomenon was found to be a rational behaviour because numerous firms continually operated under decreasing returns to scale.
Keywords: D21; L23; L25; L65; 330; DEA; technical and scale efficiency; technological change; firm size; firm level data; chemical manufacturing; Chemieindustrie; Betriebsgröße; Industrieller Strukturwandel; Technische Hilfe; Skalenertrag; Deutschland